PENGARUH PERSEPSI SISWA TENTANG MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA DI SMP - . Buyung (Universitas Batanghari Jambi, 2016)
abstract: The aims of this research is to know influence the student perception about mathematics to mathematics learning outcomes in SMP.The research method uses a quantitative approach. The data collection perceptions of students about math using questionnaires and learning outcomes data using the second semester exam grades. sample taken by random sampling technique amounted to 80 students. hypotheses using correlation analysis to Phi. The results showed that r > r, because 0,390 > 0,283 then there is the influence of the students 'perception of mathematics to students' mathematics learning outcomes. This means that to get high mathematics learning outcomes is needed perception of mathematics is also high. Vice versa mathematics student learning outcomes are lower if it has a low perception of mathematics